Penggunaan Metode Contextual Teaching and Learning (CTL) dapat Meningkatkan Minat dan Kemampuan Membaca Permulaan pada Siswa Kelas I Sekolah Dasar - Sumarno, Sumarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The Use of Contextual Teaching and Learning (CTL) Metodes to Improve Motivation and Learning Outcomes for Beginning Reading in Grade 1 Students of SDN 2 Gebang in the 2019/2020 Academic Year. This research is to improve the teacher's ability to increase motivation and learning outcomes for early reading in Grade 1. This research method is the main target of first grade students with the subject of the teacher's research and the object of research is the ability to read beginning, but the Metode used is about theory ( CTL). This theory explains to us that education, learning, and guidance to children must be in students' real world situations. The results of the study can be concluded as follows: From the results of observations in the improvement of learning that has been carried out there has been an increase and progress. Improvements that occur are as follows: 1. Varied learning Metodes. 2. Students are always actively involved. 3. Students are more daring in reading.